Design an appropriate irrigation systems for non irrigated areas of KCAET farm - JITHA K. J; Sumayya A; Thulasi Mohan P. U; Dr. K. V Levan (Guide) (Tavanur 2013 Department of Irrigation and Drainage Engineering)
Design an appropriate irrigation systems for non irrigated areas of KCAET farm
Design an appropriate irrigation systems for non irrigated areas of KCAET farm